PENGARUH PROMOSI GRATIS ONGKIR DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK HEIDE TOP CUTTON SILK BY AM INDESIGN DI MSD OFFICIAL - Intan Sari; Iis Noviyanti (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
The purpose of this study is to analyze the influence of promotion and service quality on purchasing decisions for Heide Top Cotton Silk by AM Indesign products at MSD Official both partially and simultaneously. The research method used was quantitative. The sampling technique used the Rao Purba formula when the population was unknown, resulting in a sample size of 96 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, multiple regression analysis, coefficient of determination analysis, and hypothesis testing. The results of the analysis show that the value obtained from the simple regression equation Y = 2.937 + 0.931 X₁ and based on the t test between the promotion variable and the purchasing decision, the t count value is 10.558 > 1.661 t table which shows that the promotion has an effect on purchasing decisions. The results of the analysis show that the value of the simple regression equation is obtained from the regression equation Y = 2.490 + 0.925X₂. And based on the t test between the service quality variable and purchasing decisions, the t count value is 13.797>1.661 t table shows that service quality influences purchasing decisions. The results of the analysis show that the value of the multiple regression equation is ???? = 1.575 + 0.318????₁ + 0.703????₂ and based on the f test between promotion, service quality and purchasing decisions, the F count value is 98.492> 3.090 F table which is supported by the adjusted R Square value of 0.688. These results indicate that 68.8% means that the influence of promotion and service quality variables simultaneously influences the purchasing decision variable and the remaining 31.2% is influenced by other variables.